Corepresentation of Grammatical Structure. - Kac, Michael B. (University of Minnesota Press, 1978)
This monograph in linguistics presents a nontransformational model of generative grammar called corepresentational grammar. A corepresentational description of a language consists of a set of principles on the basis of which information pertaining to abstract relations among elements of a sentence may be extracted directly from surface structure. The resulting theory provides solutions to a variety of problems pertaining to word order, complementation, complex nominals, and coordinate structures.